Environmental, health, and safety portable handbook - Woodside, Gayle (McGraw-Hill, 1998)
Provides information that environmental health and safety professionals need. This book gives a single economical source of data on: regulatory programs, EHS management techniques; audits and inspections. It also provides you help with: Environmental Management and Liability; Pollution Prevention; and Waste Management, Storage, and Containment.